2015
DOI: 10.1080/00071668.2015.1062842
|View full text |Cite
|
Sign up to set email alerts
|

The effects of grape seed in the diet of the Penedes chicken, on growth and on the chemical composition and sensory profile of meat

Abstract: 1. Effect of a diet with 5% grape seed inclusion, substituting for maize compared to a standard diet, was studied in the Penedes chicken. 2. A total of 128 chickens were used, half from each sex. Individual weights and feed intake were controlled weekly from the first d to 5th week and fortnightly until the 15th week. On the 16th week, chemical analyses of meat from 16 thighs from each diet and sex were carried out, as well as a sensory analysis of meat from 24 thighs. Differences between diet and sex were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…In this study, neither linear nor quadratic trends were observed for overall feed intake of the cockerels in response to varying levels of RGP. These findings are similar to those of Francesch et al [ 21 ] who demonstrated that inclusion of 50 g/kg of grape seed in the diet of Penedes chicken did not significantly affect feed intake. These results further corroborate the results by Alm El-Dein et al [ 22 ] where dietary supplementation with up to 40 g/kg grape pomace did not affect feed intake in Inshas strain chickens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, neither linear nor quadratic trends were observed for overall feed intake of the cockerels in response to varying levels of RGP. These findings are similar to those of Francesch et al [ 21 ] who demonstrated that inclusion of 50 g/kg of grape seed in the diet of Penedes chicken did not significantly affect feed intake. These results further corroborate the results by Alm El-Dein et al [ 22 ] where dietary supplementation with up to 40 g/kg grape pomace did not affect feed intake in Inshas strain chickens.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the inclusion of RGP as a functional ingredient in chicken diets does not compromise the palatability of the diets. There were no significant dietary influences on overall BWG and FCR, which is consistent with the findings of Francesch et al [ 21 ] and Alm El-Dein et al [ 22 ] who reported no differences on growth performance of chickens fed grape pomace diets. Similarly, Lichovnikova et al [ 23 ] reported that the diet containing RGP did not have any significant effect on growth or FCR of broiler chickens.…”
Section: Discussionsupporting
confidence: 91%
“…The supplementation of 5% grape seed to Penedes chickens did not show influences in protein, lipid and ash percentages of meat, but determined a higher percentage of unsaturated fatty acids due to linoleic acid. Concerning sensory analyses of cooked meat from the biceps femoris muscle, the inclusion of grape seed affects some parameters, giving a nuttier smell, more metallic flavour, more stringiness, less pork crackling odour, less pork crackling flavour, less sweet flavour and less broiler meat flavour [140]. These not positive effects found could be due to condensed tannins that can form complexes with proteins which are generally indigestible.…”
Section: Monogastricmentioning
confidence: 99%
“…Although there are many positive effects of plant-derived phenolic materials, some of them demonstrated negative effects as well. For example, the sensory profile of meat from chickens fed 5% grape seed meal was found to have a less sweet and more metallic flavor, while being more stringy, but overall the diet did not significantly impact the meat acceptability (86). A study on various pure extracts in poultry feed determined that anthocyanins from cherries added to poultry feed significantly increased the daily feed intake, but resulted in a slightly lower average weight, which translates to a lower feed efficiency (87).…”
Section: Potential Side Effectsmentioning
confidence: 99%